PENGELOLAAN KAIN TENUN SONGKET KHAS PALEMBANG DI DESA PEDU KABUPATEN JEJAWI KECAMATAN OGAN KOMERING ILIR (OKI) - Hidayat Hidayat; Gunadi Gunadi; Lazi Arlangga; Firda Yulianti (Universitas Ahmad Dahlan, 2020)
Abstract: Management in general can be said that the stages in carrying out or carrying out management include: planning, organizing, implementing, and controlling. The method of implementation is a general strategy adopted in the collection and analysis of data needed to answer the problem being investigated or investigated. The approach used is a qualitative approach with a descriptive method, which provides a great opportunity for researchers to describe field findings in Pedu Village. Type of qualitative research. Data collection techniques, as follows: observation, documentation, interviews. The results of this community service activity are Pedu village people who manage varied songket cloths, this activity is an effort of craftsmen to increase the attractiveness of buyers by selling songket cloth at low prices but not at a loss and changing yarn variations and motifs used in making songket. Palembang Typical Songket Woven Fabric in Pedu Village, Jejawi District, Ogan Komering Ili Regency (OKI) 2020, is expected to be one of the efforts to empower songket cloth better in the future so that it can develop rapidly.